Educação Ambiental e ecologismo nas trilhas das caminhadas ecológicas - Santos, Cássio Garcez dos (2007)
The aim of this work is to discuss the potentialities and limits of ecological hiking as a specific modality of Environmental Educational having ecologism as the theoretical reference. Thus, this study seeks to conceptualise, characterize and historicize ecological hiking, through the systematisation of information about the act of hiking and by establishing correlations with other activities such as excursionism, mountaniering and ecotourism. Based on the theoretical and conceptual framework of ecologism, the analysis problematises the practice of ecological hiking and seeks to understand it as an expression of the ecological movement and as a specific modality of Environmental Education. In order to investigate and theoretically consolidate the relation between ecological hiking, ecologism and Environmental Education, this study adopts the approach of emancipatory perspective of Environmental Education and is based on the education for critical consciousness preconised by Paulo Freire. The research is fundamented in the case study of the group Ecoando Ecologia e Caminhadas (Ecoando Ecology and Hiking) due to its longevity (thirteen years of existence) and to the fact that it proclaims itself as an ecology group. Ultimately, the work discusses the limits and the possibilities of ecological hiking as an Environmental Education practice, based on the perspective of ecologism, environmental education and the transformative praxis of the relationship between society and environment.